2007
DOI: 10.1111/j.1525-1446.2007.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Delivery of Health Care Services to Migrant Farm Worker Families Through a Community Partnership Model

Abstract: The Farm Worker Family Health Program (FWFHP) is a 13-year community partnership model designed to increase delivery of health care services for migrant farm worker families. During a yearly 2-week immersion experience, 90 students and faculty members provide health care services, including physical examinations, health screenings, health education, physical therapy, and dental care for 1,000 migrant farm workers and migrant children. Students and faculty members gain a deeper appreciation of the health and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 7 publications
0
37
0
1
Order By: Relevance
“…Founded in the models of Development in Context Evaluation or DICE (Ostrom, Lerner, & Freel, 1995) and University-CBO Collaborative Partnership or UCCP (Harper & Salina, 2000), community-based participatory research (CBPR) emphasizes the importance of partnering with community agencies to co-develop culturally sensitive assessment and intervention strategies involving important problems facing low-resource urban communities (Connor, Rainer, Simcox, & Thomisee, 2007;Minkler & Wallerstein, 2003).…”
Section: Community-based Partnershipmentioning
confidence: 99%
“…Founded in the models of Development in Context Evaluation or DICE (Ostrom, Lerner, & Freel, 1995) and University-CBO Collaborative Partnership or UCCP (Harper & Salina, 2000), community-based participatory research (CBPR) emphasizes the importance of partnering with community agencies to co-develop culturally sensitive assessment and intervention strategies involving important problems facing low-resource urban communities (Connor, Rainer, Simcox, & Thomisee, 2007;Minkler & Wallerstein, 2003).…”
Section: Community-based Partnershipmentioning
confidence: 99%
“…These programs and resources may help to bridge the gap between health care providers and migrant farmworkers and improve the effectiveness of efforts to educate and promote health (Migrant Health Promotion, 2011). A community partnership model is another proven method of increasing delivery of health care to migrant farm worker populations (Connor, Rainer, Simcox, & Thomisee, 2007). Migrant health centers collaborate with colleges and universities to provide health professions students an educational, cultural, and enlightening clinical experience.…”
Section: Health Statusmentioning
confidence: 99%
“…Community-academic partnership models of community health increase students' cultural competency and awareness of social responsibility. The partnership provides for a variety of services including health education, health screening, dental hygiene, and body mechanics education (Connor et al, 2007).…”
Section: Health Statusmentioning
confidence: 99%
“…The IOM 2002 report concluded that collaborations are becoming more common in public health practice [2]. A number of studies suggest that collaborations are a viable strategy as LHDs are actively partnering with different entities/stakeholders in their communities to address public health issues [6,8,23-25]. …”
Section: Introductionmentioning
confidence: 99%